2020
DOI: 10.1017/s0022029920000266
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physico-chemical changes in UHT milk during storage at different temperatures

Abstract: This research communication describes enzymatic and physico-chemical changes during storage of UHT milk. The UHT milk sample was stored at 5 and 30°C for 4 months and analyzed regularly at intervals of one month. During storage of UHT milk, there was a significant (P < 0.001) increase in non-protein nitrogen, non-casein nitrogen, soluble calcium, soluble magnesium and proteolysis, while a significant (P < 0.001) decrease in pH was observed. There was a slight change in the particle size and zeta potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Moreover, the acidity increment rate was more pronounced in the UHT milk filled into the pouch versus Tetra Brik. Further, the TA % increase rate of UHT milk was at 25 °C higher than that occurred at 5 °C, which is in concurrence with Ranvir et al (2020). -Water-soluble nitrogen (WSN).…”
Section: Physicochemical Changes Of Uht Milk Along With Storagesupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, the acidity increment rate was more pronounced in the UHT milk filled into the pouch versus Tetra Brik. Further, the TA % increase rate of UHT milk was at 25 °C higher than that occurred at 5 °C, which is in concurrence with Ranvir et al (2020). -Water-soluble nitrogen (WSN).…”
Section: Physicochemical Changes Of Uht Milk Along With Storagesupporting
confidence: 77%
“…According to the methodology described by Snedecor and Cochran (1980) and using factorial analysis followed by Duncan's Multiple Range Test, the statistical analysis was performed with probability ( p < 0.05) being considered statistically significant. SAS software (SAS, 1996) was used to conduct statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical examinations of colostrum samples were estimated as follows: The samples' pH was determined using a pH meter in accordance with the procedure described in [7], the colostrum's specific density was determined using a Lactometer in accordance with the procedure described in [8], and the samples' viscosity was determined using a viscometer by comparing the flow rate of a known volume of colostrum to the flow rate of the same volume of water at 20 ° C [9].…”
Section: Physical Examinationsmentioning
confidence: 99%
“…The rate of these changes is largely dependent on the storage time and temperature. They cause adverse impact on the quality of UHT milk, thus limiting consumer acceptance (Corredig and Dalgleish, 1996;Richards et al 2014;Sakkas et al 2014;Deeth and Lewis, 2017;Ranvir et al 2020b). Some of the researchers reported that during storage of UHT milk, there occurs reduction in sweet taste and development of sugary aromatic flavor (Clare et al 2005;Jensen et al 2015).…”
Section: Introductionmentioning
confidence: 99%